EPIDEMIOLOGY OF HYPERTENSIVE DISORDERS OF PREGNANCY IN INDIA - SNEHA, SHRUTI; RIGVEDA, RICHA; SHARMA, NALNEESH (International Journal of Current Pharmaceutical Research, 2023)
Objective: Hypertensive disorders of pregnancy (HDP), including gestational hypertension, preeclampsia, and eclampsia, are a global concern due to their impact on maternal and fetal health. The epidemiological landscape of HDP in India, a diverse and populous nation, presents unique challenges influenced by healthcare disparities and cultural factors. Methods: This cross-sectional study, conducted from Jul 1, 2018, to Jun 30, 2019, aimed to compare the spot urinary protein/creatinine ratio with the conventional 24 h urine protein collection method for proteinuria estimation in preeclamptic pregnant women. Ninety inpatients were included, adhering to specific inclusion and exclusion criteria. Data on demographics, blood pressure, liver function, and 24 h urine protein excretion were collected and analyzed statistically. Results: The mean age of pregnant women with preeclampsia in India was 28.9 y (range: 18-33), with 45.55% primigravida and 65.55% multigravida. Diastolic blood pressure at admission was 94.98 mmHg±8.54, displaying variations compared to other studies, potentially influenced by genetic, dietary, and healthcare factors. Liver function test results indicated abnormal findings in 90% of cases for total bilirubin, 60% for alanine transaminase (ALT), and 60% for aspartate transaminase (AST), highlighting disparities in liver function when compared to prior research. Proteinuria levels demonstrated substantial variation, with the present study reporting a mean 24 h urine protein excretion of 1884 mg/d±2562, reflecting the complexity of proteinuria assessment across different populations and methodologies. Conclusion: The epidemiology of HDP in India is intricate and multifactorial, influenced by diverse demographic factors, blood pressure levels, liver function, and proteinuria. Findings underscore the need for region-specific research and tailored healthcare interventions. Further investigations are essential to unravel the contributing factors to HDP in India and guide effective preventive measures and management strategies in this populous and diverse nation.